Dietary behaviours during pregnancy: findings from first-time mothers in southwest Sydney, Australia - Simpson Judy M; Flood Victoria M; Wen Li; Rissel Chris; Baur Louise A (BMC, 2010)
Abstract Background Limited prevalence data are available for nutrition related health behaviours during pregnancy. This study aimed to assess dietary behaviours during pregnancy among first-time mothers, and to investigate the relationships between these behaviours and demographic characteristics, so that appropriate dietary intervention strategies for pregnant women can be developed. Method An analysis of cross-sectional survey was conducted using data from 409 first-time mothers at 26-36 weeks of pregnancy, who participated in the Healthy Beginnings Trial conducted in southwestern Sydney, Australia. Dietary behaviours, including consumption of vegetables, fruit, water, milk, soft drinks, processed meat products, fast foods/take away and chips, were assessed using the New South Wales Health Survey questionnaire through face-to-face interviews. Factors associated with dietary behaviours were determined by logistic regression modeling. Log-binomial regression was used to calculate adjusted risk ratios (ARR). Results Only 7% of mothers reported meeting the recommended vegetable consumption and 13% reported meeting the recommended fruit consumption. Mean and median intakes per day were 2.3 (SD 1.3) and 2 serves of vegetables, and 2.1 (SD 1.4) and 2 serves of fruit respectively. About one fifth of mothers (21%) reported drinking 2 cups (500 ml) or more of soft drink per day and 12% reported consuming more than 2 meals or snacks from fast-food or takeaway outlets per week. A small percentage of mothers (5%) had experienced food insecurity over the past 12 months. There were significant inverse associations between water and soft drink consumption (Spearman's ρ -0.20, P < 0.001), and between fruit and fast food/takeaway consumption (Spearman's ρ -0.16, P = 0.001). The dietary behaviours were associated with a variety of socio-demographic characteristics, but no single factor was associated with all the dietary behaviours. Conclusions There were low reported levels of vegetable and fruit consumption and high reported levels of soft drink and takeaway/fast food consumption among pregnant women. Dietary interventions to prevent adverse health consequences need to be tailored to meet the needs of pregnant women of low socio-economic status in order to improve their own healthy eating behaviors. Increasing water and fruit consumption could lead to reduced consumption of soft drink and takeaway/fast food among pregnant women. Trial Registration HBT is registered with the Australian Clinical Trial Registry (ACTRNO12607000168459)